2012
DOI: 10.1074/jbc.m112.377481
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor Hsf1 Cooperates with ErbB2 (Her2/Neu) Protein to Promote Mammary Tumorigenesis and Metastasis

Abstract: Background:The role of Hsf1 in mammary tumorigenesis and metastasis remains elusive. Results: Hsf1 deletion inhibits mammary tumorigenesis and metastasis by reducing ERK1/2 activity and epithelial-mesenchymal transition of mammary epithelial cells. Conclusion: Deletion of Hsf1 in mice carrying Her2/Neu significantly reduces breast cancer and metastasis. Significance: These findings indicate a powerful inhibitory effect conferred by Hsf1 in ErbB2-induced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 51 publications
17
92
0
2
Order By: Relevance
“…Recent reports indicated that Hsp90 inhibitors induced HSF 1-dependent expression of Hsp7044, and the genetic deletion of HSF 1 reduced the association of Hsp90 with its kinase client proteins4546. It was also reported that the induction of Hsp70 is the biomarker of Hsp90 with N-terminal inhibition367.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports indicated that Hsp90 inhibitors induced HSF 1-dependent expression of Hsp7044, and the genetic deletion of HSF 1 reduced the association of Hsp90 with its kinase client proteins4546. It was also reported that the induction of Hsp70 is the biomarker of Hsp90 with N-terminal inhibition367.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that HSF1 promotes EMT in breast cancer cells through a mechanism that requires HER2 [30, 31]. As ovarian cancer cells typically spread throughout the peritoneal cavity in the form of 3D spheroids [32], culturing ovarian cancer cells as spheroids is likely to better mimic the in vivo growth conditions as compared to conventional 2D culturing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Hsf1 and its downstream targets, Hsps, during early central nervous system development, NC induction, or EMT has not been extensively investigated. However, we have recently found that ablation of Hsf1 leads to a reduction in EMT and metastasis in ERBB2-expressing mammary tumors as evidenced by the reduction in Snail/Slug expression and an increase in the expression of E-cadherin , suggesting that Hsf1 activity and Hsp expression is required for EMT (Xi et al, 2012). …”
Section: Discussionmentioning
confidence: 99%